Are the "nations" present in Matthew? - Jackson, Glenna S. (Hervormde teologiese studies, 2000)
Traditionally, Matthew 28:16-20 has been placed in the context of a mandate to Christianize the world. This study attempts to ascertain if the gentile women in the geneology and the Canaanite woman near the center of Mathew's gospel constitute a precedent and a model for the mandate to bring the enemy tubes into the fold of Israel.